Analysis of Factors Determining Job Satisfaction of ASN Family Planning Instructors at the Office of Women's Empowerment, Child Protection, Population Control and Family Planning (Dp3ap2kb) Bogor Regency - Vidia Nurfilyani Purwanto; Sri Lestari Prasilowati (Masterpiece, 2026)
Job satisfaction plays a vital role in determining employee performance and organizational effectiveness, particularly among Civil Servant Family Planning Instructors who are responsible for achieving population control and family welfare targets. In Bogor Regency, the relatively low achievement of family planning program outcomes indicates potential issues related to job satisfaction. This study aims to analyze the factors determining job satisfaction among Civil Servant Family Planning Instructors at the Office of Women’s Empowerment, Child Protection, Population Control, and Family Planning (DP3AP2KB) of Bogor Regency. The examined factors include salary, coworker relationships, workload, and career development, with career development positioned as an intervening variable. This research employed a quantitative descriptive approach involving 118 civil servant instructors distributed across 40 districts in Bogor Regency. Data were collected using structured questionnaires and analyzed through multiple regression analysis and Sobel tests to assess both direct and indirect effects among variables. The findings reveal that salary, coworker relationships, workload, and career development have positive and statistically significant effects on job satisfaction. Furthermore, career development significantly mediates the relationship between salary, coworker relationships, workload, and job satisfaction, indicating its strategic role in strengthening employee satisfaction. These results underscore the importance of fair compensation, supportive work relationships, manageable workloads, and clear career advancement opportunities in enhancing job satisfaction among family planning instructors. This study contributes to the public sector human resource management literature by providing empirical evidence on the determinants of job satisfaction among civil servant instructors and offers practical insights for DP3AP2KB in formulating policies to improve employee satisfaction and program performance.